JOSEPH-NICOLAS-PANCRACE ROYER'S CREATIVE WORK IN THE CONTEXT OF FRENCH MUSICAL ART DEVELOPMENT IN THE FIRST HALF OF THE 18TH CENTURY - Shevchenko, Dmytro (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study. The article attempts to systematize available information about the French composer of the first half of the 18th century P. Royer and to comprehend his role in the history of French musical art. Despite the artist's active creative, pedagogical, and public activities, his work still remains on the periphery of research interests. However, his harpsichord music is cherished by performers and listeners due to its genre diversity and vivid thematicism. The main objective of the article is to determine Royer's role in the history of French musical culture and to investigate how the artistic processes of professional French musical art in the first half of the 18th century are reflected in his creative work. The methodology includes the biographical method (studying P. Royer's life and work), genre-stylistic analysis (characterizing the composer's works), and the method of generalization. Results and conclusions. The study shows that Royer's life and work were shaped by the sociocultural and aesthetic changes of the era. At the beginning of the 18th century in Paris, Italian music was very present, which significantly influenced the development of the French national musical style. Royer's career testifies to the composer's high status and recognition of his merits. As a harpsichord teacher at court, composer, director of the Concert Spirituel, and general director of the Royal Academy of Music, Royer significantly influenced the development of French art in the 18th century. The beginning of the 18th century marked the culmination period of French harpsichord music development, the time of iconic works by F. Couperin, J.-P. Rameau, and other masters. In this context, Royer publishes his Premier livre de pièces pour clavecin in 1746, a collection consisting of fourteen brilliant pieces with characteristic programmatic titles. The composer's contribution to the harpsichord repertoire and traditional performance practice has been analyzed, revealing the peculiarities of how artistic tendencies are reflected in his works and their influence on musical writing. Combining French refinement and Italian expression, Royer's keyboard creativity marked the final wave of French harpsichord music and became a distinctive mirror of the stylistic changes of the era.